A 'paradox of the Commons'? : The planning and everyday management of Green Point Park - De Vries, Leani (Department of Environmental and Geographical Science, 2017)
Cape Town's Green Point Park is a legacy of the 2010 FIFA World Cup, built on the then dilapidated, former Common. Initially heavily contested, it is now a beautiful, popular, and well-used public space that attracts diverse people from all over the city. The thesis narrates its paradoxical story by drawing on historical and archival data, park observations, a transect walk, as well as qualitative interviews with city planners, park management, service providers, and the formerly sceptical local public. First, the thesis reflects on the conflictual planning process that led to this new urban park and a changed vision and function for the Common. Second, it explores the park's everyday operation, the management and maintenance that are central to its present acceptance and safe, clean and pristine condition. I argue that the City's planning 'by exception' of the park, and the public-private management vehicle is central to its success and differentiates it from how others operate in the city. I suggest that this neoliberally planned and managed public park produces a paradox: it has restored this space once again as a usable and accessible public 'common'. This argument challenges a literature that assumes neoliberal forms of planning and regulation to limit, at best, or destroy urban spaces, resulting in a similar 'tragedy of the commons' (Hardin, 1968) or 'end of public space' (Sorkin, 1992; Mitchell, 1995). In contrast, the thesis builds on Jerram's (2015) critique in that the traditional commons too often become 'historical fantasy,' a theorised ideal and almost impossible reality, in the contemporary neoliberal era. This more nuanced assessment of the contemporary commons is important in the South African urban context, where there is great concern that neoliberal, market-led, world city agendas perpetuate exclusion and historical legacies of segregation (Marais, 2013). In a 'paradox of the commons', this publicly regulated, privately maintained free-to-the-public park has restored what was previously a Commons, albeit an unsafe and largely unused space. The Green Point Urban Park suggests a need to 'rethink' parks and their planning and management in contemporary and neoliberal post-apartheid South Africa. They do not necessarily result in a certain 'tragedy of the commons' or 'end of public space'.